A low cost, simplified and battery-powered mobile electrophoresis system suitable as edutainment tool. - Chin, Jason Kee Chian; Kah, Hay Yuen; Sieo, Chin Chin; Yiap, Beow Chin (Science Explorer Publications, 2013)
Electrophoresis originated since 1807 and has been a staple tool used by biologist and chemist over the centuries since its inception. From paper electrophoresis system to today’s modern automated electrophoresis system, the development of electrophoresis systems have been driven by the advancement of technology and also by the requirement of better and faster resolution of results. This paper reviews the progress of electrophoresis over the decades and into possible future development of electrophoresis.